Preferences Regarding and Communication About End-of-Life Care Among Older Iranian-American Adults. (October 2019) - Rahemi, Zahra; Dunphy, Lynn M.; Newman, David
Using a cross-sectional study, this article addresses end-of-life (EOL) care for older Iranian-American adults. The purposes are twofold: (a) to explore participants' preferences for home or hospital care in the event they face EOL conditions and (b) to learn how participants prefer to communicate these preferences. Results showed that about half of the 130 participants had communicated their EOL care preferences through written documents and/or verbal discussions. A set of factors predicted the preferences (χ 2 (9) = 17.42, p < .042) and communications (χ 2 (9) = 19.54, p = .021). Regression models indicated that higher scores of social support ( p = .013) and greater numbers of cohabitants ( p = .021) were associated with a preference for home care, and experience of a loved one's death was associated with participants being willing to communicate their preferences for type of care ( p = .015). This study can bridge the gap between culturally diverse older adults' preferences and types of EOL care they ultimately receive.